Hubungan Pola Makan Dan Pemakaian Masker Terhadap Pencegahan COVID-19 Di Kecamatan Tulis Kabupaten Batang Jawa Tengah - Merita Yuliyani; Nur Endah Wahyuningsih; Mursid Rahardjo (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2022)
The COVID-19 pandemic has not yet stopped until the spread of COVID-19 has spread, including in Indonesia. Tulis District wis one of the areas with the most COVID-19 cases in Batang Regency, Central Java Province. Covid prevention factors could be influenced by internal factors and external factors. This study aims to analyze the factors related to preventing the spread of Covid in the community in Tulis District. This research is observational with a case control design. A total of 100 people with systematic sampling. Data were analyzed using Chi-Square test and Odds Ratio test. The results showed that there was a relationship between an unbalanced diet (OR = 3.857; CI = 1.670-8.911; p = 0.002), and less habit of wearing masks (OR = 2.923; CI = 1.245-6.865; p = 0.022) with the lack of prevention of the spread of Covid in the Tulis District. So that eating patterns and the habit of wearing masks are factors related to preventing the spread of COVID-19 in Tulis District.